Overexpression of SbSI-1, A Nuclear Protein from Salicornia brachiata Confers Drought and Salt Stress Tolerance and Maintains Photosynthetic Efficiency in Transgenic Tobacco - Kumari, Jyoti; Udawat, Pushpika; Dubey, Ashish K.; Haque, Md Intesaful; Rathore, Mangal S.; Jha, Bhavanath (Frontiers in Plant Science, 2017)
A novel Salicornia brachiata Salt Inducible (SbSI-1) gene was isolated and overexpressed in tobacco for in planta functional validation subjected to drought and salt stress. SbSI-1 ¬is a nuclear protein. The transgenic tobacco overexpressing SbSI-1 gene exhibited better seed germination, growth performances, pigment contents, cell viability, starch accumulation, and tolerance index under drought and salt stress. Overexpression of SbSI-1 gene alleviated the build-up of reactive oxygen species (ROS) and curtailed the ROS-induced oxidative damages thus improved the physiological health of transgenic tobacco under stressed conditions. The higher activities of antioxidant enzymes, lower accumulation of ROS, higher membrane stability, relative water content, and polyphenol contents indicated the better survival of the transgenic tobacco than wild-type (WT) tobacco under stressed conditions. Transgenic tobacco had a higher net photosynthetic rate, PSII operating efficiency, and performance index under drought and salt stress. Higher accumulation of compatible solutes and K+/Na+ ratio in transgenic tobacco than WT showed the better osmotic and redox homeostasis under stressed conditions. The up-regulation of genes encoding antioxidant enzymes (NtSOD, NtAPX, and NtCAT) and transcription factors (NtDREB2 and NtAP2) in transgenic tobacco under stressed conditions showed the role of SbSI-1 in ROS alleviation and involvement of this gene in abiotic stress tolerance. Multivariate data analysis exhibited statistical distinction among growth responses, physiological health, osmotic adjustment, and photosynthetic responses of WT and transgenic tobacco under stressed conditions. The overexpression of SbSI-1 gene curtailed the ROS-induced oxidative damages and maintained the osmotic homeostasis under stress conditions thus improved physiological health and photosynthetic efficiencies of the transgenic tobacco overexpressing SbSI-1 gene.